Simulation of many-body dynamics using Rydberg excitons. (1st July 2022) - Taylor, Jacob; Goswami, Sumit; Walther, Valentin; Spanner, Michael; Simon, Christoph; Heshami, Khabat
Abstract: The recent observation of high-lying Rydberg states of excitons in semiconductors with relatively high binding energy motivates exploring their applications in quantum nonlinear optics and quantum information processing. Here, we study Rydberg excitation dynamics of a mesoscopic array of excitons to demonstrate its application in simulation of quantum many-body dynamics. We show that the Z 2 -ordered phase can be reached using physical parameters available for cuprous oxide (Cu2 O) by optimizing driving laser parameters such as duration, intensity, and frequency. In an example, we study the application of our proposed system to solving the maximum independent set problem based on the Rydberg blockade effect.